Factors Affecting the Academic Achievement of the Students in Community Campuses - Chapagai, Shiva Dutta (KMC Journal, 2024)
Academic achievement holds significant importance in education as well as in the learning process representing the level at which both teachers and the students attain educational goals. This study aims to identify the factors influencing academic achievement among students on community campuses. The descriptive survey research design was employed. By using the purposive sampling method, four community campuses were selected out of ten community campuses from Tanahun district of Nepal. A total of 359 respondents were selected from 2479 students across the selected campuses, employing a survey with Five-Points Likert scaling technique conducted through Google form. Descriptive statistics was applied to analyze the gathered data. The finding indicated that home-related factors, campus facilities, the teaching-learning environment and resources, habits of students, teacher-student relations, and institutional factors significantly affect students' academic achievement at the university level. The study provides valuable insights for educators, policymakers, and institutions to improve the academic achievement of students.